PERSEPSI PASIEN KELAS III PBI DAN NON-PBI TERHADAP PELAYANAN RAWAT INAP DI RSUD dr. M. YUNUS BENGKULU - Johan; Tjahjono Kuntjoro; Rizaldy Pinzon (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Management of Public Hospital of dr. M. Yunuscontinues to strive on improving services quality for their patient,although the result has not been optimal. It demonstrated onachievement of Bed Occupancy Rate (BOR) of the 3rd inpatientclass in 2014 still 44,25% (Standard BOR by Health Ministry is60-85%) means most hospital bed have not utilized and patientnumber of the 3rd inpatient class showed decreasing from5.486 in 2013 becomes 3.813 in 2014. Objectives: Identifying perception of the 3rd class patienttowards inpatient services in dr. M. Yunus Public HospitalBengkulu, to know are there differences in perception betweeninsurance contribution and non-insurance contribution. Methods: This study was analytical observational researchusing cross sectional approach. Number of respondents of thisstudy were 130 patient as beneficiaries of health insurance and130 patient as non-beneficiaries of health insurance. Samplewas determined by proportional random sampling. The analysisused chi square test and qualitative data. Results: Patient perception to quality of service to come cut ofpaint 25.99 when compared to the cut of point / mean theoretical25 is categorized good results. The relationship between patientperception PBI towards service quality results are statisticallysignificant p < 0.05. OR value of 2:13 means that the patient'sperception PBI towards service quality is better than the 2:13time patients NonPBI. Patients' perceptions towards skills ofofficers of 26.17 when compared to the cut of point/meantheoretical 25 is categorized good results. The relationshipbetween the patient's perception PBI towards perceptions ofskills results are significant p < 0.05. Practically obtained ORvalue 1.87 means that the patient's perception towards skills ofofficers PBI better by 1.87 times compared to patients NonPBI. Conclusion: Perception of the third-class patient PBI and Non-PBI towards third class inpatient services has been good. Thereis a difference of perceptions between the groups of patientsPBI with NonPBI patient groups.